Bentuk dan Konstruksi Komposisi Musik Modern ‘Tjapung Ketjipung Di Tjikapundung’ Karya Amir Pasaribu - Ance Juliet; Emmi Simangunsong (LPPM Universitas HKBP Nommensen, 2022)
This research is entitled Modern Music Composition 'Tjapung Ketjipung Di Tjikapundung' by Amir Pasaribu. The basic method that applied in this research is descriptive method. In addition, the approach used by the library method is to find and produce pentatonic elements similar to the pelog barrel which are harmonized with elements of western tone harmony in the composition of Tjapung Ketjipung in Tjikapundung which is famous for the work of the Indonesian composer Amir Pasaribu with the characteristics of his piano music, regarding the form and the pattern of the structure as well as the parts contained in the construction of the music, the beginning, the continuation part, the complication part and the resolution part. In addition to the musical construction, the composition of piano music by Amir Pasaribu uses a free form pattern in the context of modern music. The use of chord levels (harmony progressions) and soloist playing made this composition even more exalted and majestic for its time.